ASSESSMENT OF AVAILABILITY OF STREET LIGHT SYSTEM: A STUDY OF WARRI, DELTA STATE, NIGERIA (Nigerian Journal of Technology, 2020)
The study computes the availability of street lighting system in Warri. This system under study consists of subsystems that are known as workstations. A generator and sets of street light make up a workstation. The power source and the street lighting were modeled into series and parallel combinations. Reliability Block Diagrams and Path Tracing Method were employed assuming independent failure of the components. The availability of the set of street lightings, workstations and hence the availability of the system were determined. Results of the study show that users in Cemetery road had the least availability of 62.19% for the period. The implication is that users travelling along this road experienced wide variation of light that could lead to accidents. http://dx.doi.org/10.4314/njt.v39i2.24